2011
DOI: 10.1111/j.1744-7917.2011.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive associations between total body color dimorphism and climatic stress‐related traits in a stenothermal circumtropical Drosophila species

Abstract: Low desiccation resistance of Drosophila ananassae reflects its rarity outside the humid tropics. However, the ability of this sensitive species to evolve under seasonally varying subtropical areas is largely unknown. D. ananassae flies are mostly lighter during the rainy season but darker and lighter flies occur in the autumn season in northern India. We tested the hypothesis whether seasonally varying alternative body color phenotypes of D. ananassae vary in their levels of environmental stress tolerances an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…We speculate that the initial composition and change in the cuticle layer is more biased towards a greater number and length of hydrocarbons in H. borealis than either Antarctic dipteran. Differences in melanization between the two Diptera may also offer an explanation for the differing levels of resistance in the current study, as has been shown between Drosophila Parkash et al 2009;Parkash et al 2012;Ramniwas et al 2013).…”
Section: Desiccation Resistancesupporting
confidence: 57%
“…We speculate that the initial composition and change in the cuticle layer is more biased towards a greater number and length of hydrocarbons in H. borealis than either Antarctic dipteran. Differences in melanization between the two Diptera may also offer an explanation for the differing levels of resistance in the current study, as has been shown between Drosophila Parkash et al 2009;Parkash et al 2012;Ramniwas et al 2013).…”
Section: Desiccation Resistancesupporting
confidence: 57%
“…The laboratory-selected desiccation-resistant and -sensitive strains of D. melanogaster have shown similar amounts of cuticular lipid mass (Gibbs et al, 1997), and there is also a lack of differences in the amount of cuticular lipid mass in northern versus southern populations of D. melanogaster (Parkash et al, 2008a). However, in two cases (Melanoplus sanguinipes and Z. indianus), there are significant intrapopulation differences in the amount of cuticular lipid mass per cm 2 (Rourke, 2000;Parkash et al, 2008a;Parkash et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Phenotypic variation of body melanisation in some lepidopterans and coelopterans are represented by discrete morphs (melanic and nonmelanic) consistent with a major locus (Da Cunha, 1949;Martinez and Cordeiro, 1970). Several studies have shown changes in the frequencies of two or more allelic variants in response to temporally or spatially variable climatic conditions (Umina et al, 2005;Parkash et al, 2009;Parkash et al, 2012). In contrast, variation in body melanisation in a D. melanogaster population follows a bell-shaped curve and such a quantitative trait is expected to respond quickly to laboratory as well as field selection.…”
Section: Introductionmentioning
confidence: 99%
“…All acclimation experiments were carried out on 10 homozygous (for phenotype) strains for the dark as well as light morphs (see Parkash et al, 2012). These strains were originally derived from true breeding (for body color) iso-female lines from Solan.…”
Section: Acclimation Treatmentsmentioning
confidence: 99%
“…The adult acclimation for cold resistance in D. melanogaster increases the lifespan, reduces mortality and recovery time after exposure to subzero temperatures (Rako and Hoffmann, 2006;Le Bourg, 2007). Further, the dark morph of D. ananassae is more resistant to cold and desiccating conditions as compared to the light morph; while the latter is more resistant to heat stress (Parkash et al, 2012). Thus, we may expect evolutionary responses to natural selection on traits related to desiccation and cold stress in subtropical populations of D. ananassae.…”
Section: Introductionmentioning
confidence: 96%